Wanprestasi Dalam Transaksi Jual Beli Sapi Di Desa Polagan Kecamatan Galis Kabupaten Pamekasan - Dewi Tri Lusiyana Agustin; Keisya Ayudha Wianto (JOURNAL SAINS STUDENT RESEARCH, 2023)
The journal we created is entitled “DEFENSE IN THE SALE AND PURCHASE TRANSACTION OF CATTLE IN POLAGAN VILLAGE, GALIS DISTRICT, PAMEKASAN DISTRICT”. And bind himself in an agreement. In the case study of this journal, the buyer is suspected of having committed a default because the buyer did not fulfill his obligations and did not pay the seller’s rights. There are problems in this article, in order to find out what factors caused the buyer to have defaulted and resulted in the seller experiencing material losses and to find out how to resolve non-performance in the cattle sale and purchase contract between the buyer and the seller. The research method in this article is a type of Empirical Legal research which is a method which uses facts taken from human behavior, both obtained from verbal behavior and real behavior carried out through direct observation. The nature of this article is to use a Descriptive Analysis approach, which is a method that aims to create a description of an object and the fact that the buyer has not fulfilled his obligations to the seller in paying the remaining price of the cow that is still owed at the time promised and agreed upon. Factors that cause the buyer not to fulfill their obligations to the seller are due to negligence and the existence of the seller being the main factor, the buyer has not fulfilled his responsibility to pay so that losses are incurred by the seller.